Réponses

2013-11-08T20:31:44+01:00
Bonsoir

A= (2x -1)² + (x +1 )²
A = (4x² -4x +1) + (x² +2x +1)
A = 4x² -4 x+1 +x² +2x +1
A = 5x² -2x +2

B= 2(1-x)(2x + 7 )
B = (2 -2x)(2x+7)
B = 4x +14 -4x -14x
B = -14x +14

C= x+2(x - 5) +8 (3-2x)
C = x + (2x-10) + (24 -16x)
C = x +2x -10 +24 - 16x
C = -13x +14

D=(x -1)(x+2) - (2x+5)²

D = x² +2x -x -2 - (4x² +20x+25)
D = x² +2x -x -2 -4x² -20x -25
D = -3x² -19x -27

2013-11-08T20:42:05+01:00
1) Développer :
A= (2x -1)² + (x +1 )²
=4x²-4x+1+x²+2x+1
=5x²-2x+2

B= 2(1-x)(2x + 7 )
=2(2x+7-2x²-7x)
=4x+14-4x²-14x
=-4x²-10x+14

C= x+2(x - 5) +8 (3-2x)
=x+2x-10+24-16x
=-13x+14

D=(x -1)(x+2) - (2x+5)²
=x²+2x-x-2-(4x²+20x+25)
=x²+2x-x-2-4x²-20x-25
=-3x²-19x-27